Electrosynthesis of ZrO2 Nanoparticles with Enhanced Removal of Phenolic Compound - Muhammad Farhan, Hanafi; Norzahir, Sapawe (Elsevier Ltd., 2019)
The electrogenerated zirconia (EGZrO2) catalyst was prepared via simple electrochemical method. The photoactivity of the catalyst was examined by photodegradation of phenol under varying pH, catalyst dosage, and initial concentrations. An amount of 0.40 g/L EGZrO2 was found to be the optimum dosage for 10 mg/L phenol, which gave almost complete photodegradation (98) of phenol after 1 h under visible light irradiation at pH 9 and room temperature. These photoactivity were compared to commercial TiO2 and commercial ZrO2 which give approximately 80 and 78, respectively. Photolysis was also conducted as control which resulted in 2 degradation. Therefore, in this study, it is believed that the electrochemical method system could improve the properties of EGZrO2 catalyst, and finally led to higher efficiency of its performance toward phenol degradation